Anaemia management with C.E.R.A. in routine clinical practice: OCEANE (Cohorte Mircera patients non-dialysés), a national, multicenter, longitudinal, observational prospective study, in patients with chronic kidney disease not on dialysis. Issue 3 (9th March 2013) - Frimat, Luc; Mariat, Christophe; Landais, Paul; Koné, Sébastien; Commenges, Bénédicte; Choukroun, Gabriel
Abstract : Objective: The aim of this study was to describe the management of anaemia with a continuous erythropoietin receptor activator (C.E.R.A., methoxy polyethylene glycol epoetin-β), in patients with chronic kidney disease (CKD) not on dialysis, naïve or non-naïve to treatment with erythropoiesis-stimulating agents (ESAs) at inclusion. Design: National, multicentre, longitudinal, observational prospective study. Setting: 133 nephrologists practicing in France selected patients during their routine follow-up visits. The study was non-interventional. Participants: They were adult CKD patients not on dialysis or kidney transplant patients, naïve or not to ESA treatment: 524 patients not on dialysis (48% ESA-naïve) and 92 kidney transplant patients (24% ESA-naïve) were included and followed up every 3 months during 1 year. Outcome measures: The two main endpoints were the percentage of patients who achieved target haemoglobin (Hb) levels as per European Medicines Agency guidelines (10–12 g/dl) around 6 months of treatment and modalities of treatment. Results: Approximately one in two patients had an Hb level within 10–12 g/dl at baseline, and around 6 and 12 months of treatment. Ninety per cent of ESA-naïve patients achieved at least +1 g/dl increase over baseline Hb levels or had Hb within 10–12 g/dl around 6 and 12 months. The Hb level remained at approximately 11.5 g/dl during the 12 months of follow-up. Around 6 months: almost all patients were receiving a once-monthly subcutaneous dose of C.E.R.A. (patients not on dialysis: 95±54 µg; kidney transplant patients: 121±70 µg); approximately half the patients did not require a change in C.E.R.A. dose. Adverse effects related to C.E.R.A. were observed in less than 5% of patients and led to modification or discontinuation of treatment in 2%. Conclusions: The efficacy and safety of C.E.R.A. in CKD patients not on dialysis, with or without kidney transplantation, were confirmed in routine clinical practice.